Transcriptome and translatome profiling of Col-0 and grp7grp8 under ABA treatment in Arabidopsis - Jing Zhang; Yongxin Xu; Jun Xiao (Scientific Data)
Abstract Abscisic acid (ABA) is a crucial phytohormone that regulates plant growth and stress responses. While substantial knowledge exists about transcriptional regulation, the molecular mechanisms underlying ABA-triggered translational regulation remain unclear. Recent advances in deep sequencing of ribosome footprints (Ribo-seq) enable the mapping and quantification of mRNA translation efficiency. Additionally, RNA-binding proteins (RBPs) play essential roles in translational regulation by interacting with target RNA molecules, making the identification of binding sites via UV crosslinking and immunoprecipitation (CLIP) critical for understanding RBP function. Glycine-rich RNA-binding proteins (GRPs), a prominent class of RBPs in plants, are responsive to ABA. In this study, RNA-seq and Ribo-seq analyses were conducted on 3-day-old Col-0 and grp7grp8 seedlings of Arabidopsis thaliana, treated with either ABA or mock solutions. These analyses facilitated deep sequencing of total mRNA and mRNA fragments protected by translating ribosomes. Additionally, CLIP-seq analysis of pGRP7::GRP7-GFP grp7-1 identified RNA bound by GRP7. This multi-omics dataset allows for a comprehensive investigation of the plant’s response to ABA from various perspectives, providing a significant resource for studying ABA-regulated mRNA translation efficiency.